Population Migration as a Result of the War in Syria since 2011 as a Threat to International Security - Derlatka, Katarzyna E. (Social consequences of war, 2024)
This article looks at the migration wave triggered by the war in Syria since 2011 and analyses the possibility of using mass population migration to destabilise the European Union and other areas in the world to influence the geopolitical situation. Mass migration of populations can be a security threat, influencing the domestic and foreign policies of various states. The effect of using migrants for their own ends and changing the international chessboard can be seen especially in 2023. The wave of migration from Syria and then from other countries in the Middle East and Africa, has proved to be an excellent tool in Russia’s hybrid war against the West, in achieving strategic goals by using blackmail and pressure on international players, including on the war in Ukraine, in which many countries in the world are involved.